A Model of Capital Allocation, Education, and Job Choice in China. Issue 5 (2nd September 2016) - Lien, Jaimie W.; Wang, Wei; Zheng, Jie
Abstract : The narrowing wage gap between high- and low-skilled workers in the Chinese labor market in recent years is suggestive of government interventions which may have been implemented in the capital markets. We develop a game theoretic model between a continuum of heterogeneous workers and the government, where workers choose education levels, the government chooses its capital allocation strategy subject to a budget constraint, and the workers then make employment choices. The government is modeled as having a possible policy priority on particular industries or sectors. We characterize the existence and uniqueness conditions for equilibrium of the game and provide a closed form solution to the model for reasonable parameter values. We show that the wage ratio between high- and low-skilled workers decreases as government's policy priority (or bias) toward low-skilled sectors increases, up to a threshold level of the policy bias. Beyond that threshold level, the wage gap between high- and low-skill workers is negative. Thus the shrinking wage gap can be explained by the government's capital investment strategy which is driven by its policy priority bias. We derive comparative statics results and discuss policy implications.